2021
DOI: 10.3389/fmed.2021.582764
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Management to Reduce the Mortality of COVID-19: Experience From a Designated Hospital for Severely and Critically Ill Patients in China

Abstract: Background: The coronavirus disease 2019 (COVID-19) has swept through the world at a tremendous speed, and there is still limited data available on the treatment for COVID-19. The mortality of severely and critically ill COVID-19 patients in the Optical Valley Branch of Tongji Hospital was low. We aimed to analyze the available treatment strategies to reduce mortality.Methods: In this retrospective, single-center study, we included 1,106 COVID-19 patients admitted to the Optical Valley Branch of Tongji Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…15 Furthermore, dynamic cytokine storms as well as high serum IL-6 and TNF-serum levels, were found to be independent and significant predictors of disease severity and death. 4,16,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Conversely, some interleukins have been reported by studies indicating that they are not linked to the prognosis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, dynamic cytokine storms as well as high serum IL-6 and TNF-serum levels, were found to be independent and significant predictors of disease severity and death. 4,16,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Conversely, some interleukins have been reported by studies indicating that they are not linked to the prognosis of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a total of 61 peer-reviewed studies were included in the final analysis (Fig. 1A) 10,12,13,21–78 . Of these final 61 studies, 11 studies were conducted in China, 3 were conducted in America (2 studies from South America and 1 study from Central America), 17 involved centers in the United States, 16 involved centers in Europe, 3 involved centers in Canada, 9 involved centers in Asia, and 2 were based on multinational collaborations (one was between the United Kingdom and Ireland, and the second was between the United States, Europe, Canada, and Japan).…”
Section: Resultsmentioning
confidence: 99%
“…A large study in UK assessed liver fat and liver fibroinflammatory disease by MRI. The study concluded that hepatic steatosis, rather than underlying obesity, increases the risk of infection and hospitalization for COVID-19 (Zhu et al, 2021). Another study showed higher frequency of hepatic steatosis at CTscan among COVID-19-positive patients (Medeiros et al, 2020).…”
Section: Discussionmentioning
confidence: 95%